2014
DOI: 10.1016/j.bbmt.2014.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Early Failure of Frontline Rituximab-Containing Chemo-immunotherapy in Diffuse Large B Cell Lymphoma Does Not Predict Futility of Autologous Hematopoietic Cell Transplantation

Abstract: The poor prognosis of diffuse large B-cell lymphoma (DLBCL) patients relapsing within 1-year of initial diagnosis after first-line rituximab-based chemoimmunotherapy has created controversy about the role of autologous transplantation (auto-HCT) in this setting. We compared auto-HCT outcomes of chemosensitive DLBCL patients between 2000 and 2011 in two cohorts based on time to relapse from diagnosis. The early rituximab failure (ERF) cohort consisted of patients with primary refractory disease or those with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 35 publications
(44 reference statements)
5
85
1
Order By: Relevance
“…[8][9][10] Even among patients with relapsed or refractory DLBCL who respond to salvage therapy and are able to undergo ASCT, about 50% will ultimately relapse after transplantation. 11,12 The prognosis for these patients is poor, especially for those who have high-risk factors such as secondary IPI score .2 or relapse #12 months post-ASCT. 10,13 Thus, most patients with refractory DLBCL have no curative treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Even among patients with relapsed or refractory DLBCL who respond to salvage therapy and are able to undergo ASCT, about 50% will ultimately relapse after transplantation. 11,12 The prognosis for these patients is poor, especially for those who have high-risk factors such as secondary IPI score .2 or relapse #12 months post-ASCT. 10,13 Thus, most patients with refractory DLBCL have no curative treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…This supports previous observations that prior rituximab exposure did not negatively impact the outcome of patients undergoing autoSCT for DLBCL. 22,23 As our database registers only patients who were actually transplanted, this observation does not exclude the possibility that the prognosis of DLBCL failing first-line immunochemotherapy may be worse than for those receiving chemotherapy alone. The current study also confirms previous findings that patients failing to respond to salvage induction and who have relapsed within a year of first-line therapy have a worse outcome following autoSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bridging to intensification and transplantation can remain a valid strategy, as previously shown for patients responding to second-line treatment. 7,17,18 Allo-SCT could be considered in our study population, and recently an encouraging OS of 47% at 1 year was reported in aggressive lymphoma relapsing o 12 months after last line and treated with lymphomadirected myeloablative conditioning followed by allo-SCT. 19 However, most experts would restrict this option to patients relapsing after ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Still, even in the latter patients with poor prognosis relapses, ASCT remains the standard of care if patients can achieve CR/PR pretransplantation. [9][10][11] We were interested in the characteristics and survival of patients included in the CORAL study, who did not fulfill the protocol strategy at the time of evaluation before transplant. Clinicians had no per-protocol recommendation, except to complete a dedicated form at the time of withdrawal to record what was happening.…”
Section: Introductionmentioning
confidence: 99%